Sustaining Lean Creating a Culture of Continuous Improvement. - Protzman, Charles (BASICS Lean® Implementation, 2022)
Lean is about building and improving stable and predictable systems and processes to deliver to customers high-quality products/services on time by engaging everyone in the organization. Combined with this, organizations need to create an environment of respect for people and continuous learning. It's all about people. People create the product or service, drive innovation, and create systems and processes, and with leadership buy-in and accountability to ensure sustainment with this philosophy, employees will be committed to the organization as they learn and grow personally and professionally. Lean is a term that describes a way of thinking about and managing companies as an enterprise. Becoming Lean requires the following: the continual pursuit to identify and eliminate waste; the establishment of efficient flow of both information and process; and an unwavering top-level commitment. The concept of continuous improvement applies to any process in any industry. Based on the contents of The Lean Practitioners Field Book, the purpose of this series is to show, in detail, how any process can be improved utilizing a combination of tasks and people tools and introduces the BASICS Lean concept. The books are designed for all levels of Lean practitioners and introduces proven tools for analysis and implementation that go beyond the traditional point kaizen event. Each book can be used as a stand-alone volume or used in combination with other titles based on specific needs. Each book is chock-full of case studies and stories from the authors' own experiences in training organizations that have started or are continuing their Lean journey of continuous improvement. Contents include valuable lessons learned and each chapter concludes with questions pertaining to the focus of the chapter. Numerous photographs enrich and illustrate specific tools used in Lean methodology. Sustaining Lean: Creating a Culture of Continuous Improvement focuses on standard work audits, training, Lean Practitioner certification, Hoshin planning, Lean Leadership, and how to run effective meetings. The authors discuss the cultural transformation which must occur to create a Lean culture by understanding what the components are in this culture. The importance of training and the value of the person are also discussed, as is what it takes to be a Lean leader.